Effects of monetary reward and punishment on information checking behaviour. (March 2016) - Li, Simon Y.W.; Cox, Anna L.; Or, Calvin; Blandford, Ann
Abstract: Two experiments were conducted to examine whether checking one's own work can be motivated by monetary reward and punishment. Participants were randomly assigned to one of three conditions: a flat-rate payment for completing the task (Control); payment increased for error-free performance (Reward); payment decreased for error performance (Punishment). Experiment 1 ( N  = 90) was conducted with liberal arts students, using a general data-entry task. Experiment 2 ( N  = 90) replicated Experiment 1 with clinical students and a safety-critical 'cover story' for the task. In both studies, Reward and Punishment resulted in significantly fewer errors, more frequent and longer checking, than Control. No such differences were obtained between the Reward and Punishment conditions. It is concluded that error consequences in terms of monetary reward and punishment can result in more accurate task performance and more rigorous checking behaviour than errors without consequences. However, whether punishment is more effective than reward, or vice versa, remains inconclusive. Highlights: The effects of monetary reward and punishment were examined in two experiments. Reward and punishment were found to better reduce errors than control group. Reward and punishment resulted in more rigorous checking behaviour than control. Whether punishment is more effective than reward, or vice versa, remains inconclusive.